INFLUENCE OF PERFORMANCE, POLICIES AND CAREER DEVELOPMENT OF NCOS ON INTEREST IN EDUCATION REGISTRATION FORMATION OF REGULAR INDONESIAN NAVY OFFICERS - Seno Rio Utomo; Edward Sonata (JURNAL EKBIS, 2022)
The purpose of this study was to analyze the performance, policy and career development variables of the NCO on the interest in the registration of the Indonesian Navy's regular Diktukpa. The method used in this study uses quantitative methods and hypothesis testing using multiple linear regression analysis of 71 non-commissioned officers who serve on staff, KRI and Battalion. The results of the study show that performance has a significant effect on the interest in the registration of the Indonesian Navy's regular Diktukpa. The policy has a significant effect on the interest in the registration of the Indonesian Navy's regular Diktukpa. Career development has a significant effect on the interest of the Navy's regular Diktukpa and performance, policies and career development affect the interest of the Navy's regular Diktukpa registration.